Order of the Orthoprojection Widths of the Anisotropic Nikol’skii–Besov Classes in the Anisotropic Lorentz Space - Bekmaganbetov, Kuanysh Abdrakhmanovich; Toleugazy, Yerzhan (Eurasian Mathematical Journal, 2016)
In this paper we estimate the order of the orthoprojection widths of the anisotropic Nikol’skii–Besov classes in the anisotropic Lorentz space.